Consistent control strategy for CO2 refrigeration systems based on refrigerant charge management. (January 2023) - He, Yu-Jia; Tai, Ying-Di; Zhao, Xiao-Xuan; Zhang, Chun-Lu
Highlights: CO2 refrigeration systems operate in both subcritical and transcritical modes. Consistent control strategy can be independent of operation modes. Average COP losses of typical systems with new control strategy are within −0.5%. Abstract: CO2 refrigeration systems operate in both subcritical and transcritical modes throughout a year. Different control strategies have been developed under different operation modes. However, this leads to complexity in implementation. In this work, we proposed a consistent control strategy (CCS) independent of operation modes for CO2 refrigeration systems to provide stable operation in a simple way. This strategy is grounded on the fact that discharge pressure control in transcritical mode is essentially regulating refrigerant charge in a running system. The active pressure control can be avoided with fine refrigerant charge management, thereby employing the same control strategy as in subcritical mode. Through numerical simulations, the characteristics of optimum charge in three typical CO2 refrigeration configurations were identified, which are single-stage system, two-stage system, and booster system. The optimum charges of three systems under different operating conditions all vary less than 22%, particularly the booster system fluctuates by 6% only. By adopting CCS, the average COP losses for three systems are all within -0.5% relative to their ideal optimum performance. Compared with re-optimized conventional multi-zone control, the maximum deviation is -0.3%. Therefore, the proposed new strategy can achieve comparable quasi-optimum performance, while significantly simplifying control scheme. It can be an attractive solution for small units which require simple and robust control.